KAJIAN TEKNIK PERBANYAKAN VEGETATIF PISANG AMBON KUNING DENGAN PEMBELAHAN BONGGOL (CORM) - Rugayah, Rugayah; Hapsoro, Dwi; Ulumudin, Ade; Motiq, Feria Wirana (JURNAL AGROTROPIKA, 2012)
Propagation by corm division of banana provides an opportunity to get the seedling in large quantities, but need technology to promote the growth of spur on the buds that are still dormant. Research conducted in 2010 in the greenhouse of Faculty of Agriculture, University of Lampung aimed to determine the effect of growing media and concentration of BA in Yellow banana?s Ambon multiplication by corm division. The study con-sisted of 2 subtitle designed in perfectly with the design of randomized groups factorial (4x2) which is repeated 3 times. The first factor is the same in both experiments: BA concentrations (0, 50, 100, 200 mg / l) and the second factor in the first experiment: the type of media (sand mixed with rice husk and sand with compost 1:1) and in Experiment II: cleavage divition (four and eight parts). Planting material in Experiment I, hump into four sections and planting medium used in Experiment II, a mixture of sand and rice husk 1:1. The variables measured were: time emerged shoots, number of shoots, and shoot height, diameter of the base of shoots, number of leaves, leaf width, number of roots, and the average length of the roots. Data were analyzed by using a variety of software Mini Tab, followed by a test of least significant difference (LSD) 5%. The results showed that: (1) growth of shoots on a mixture of sand and compost media better than husk fuel mixture, as well as in treatment 4 parts division hump better than 8 parts. But seen the efficiency of shoot growth, division 8 section bits more efficient because it produces more shoots (4.8 shoots) without giving BA, whereas if split 4 parts need BA a concentration of 50 ppm. Giving BA 50 ppm in sand and compost to increase the number of shoots indicated for the highest percentage (91.67%). Keywords: Yellow banana?s Ambon, corm divition, benzyladenine, growing media.